Rapid resolution of severe subcutaneous emphysema causing respiratory failure with subcutaneous drain. (March 2021) - Mustafa, Ala; Heleno, Caio; Summerfield, Douglas T
This case reports on a critically ill patient (Male, 74) with severe subcutaneous emphysema which progressed to causing respiratory distress. We document both the severity of the condition we observed and then present a novel intervention. In this case, we decompressed the patient at the intensive care unit-bedside and resolved the condition. While subcutaneous emphysema is relatively common, the severity of the condition we observed, and the lack of definitive treatment guidance have prompted us to present this case as a plausible treatment guide.